2021
DOI: 10.22161/ijels.61.63
|View full text |Cite
|
Sign up to set email alerts
|

The balanced scorecard's evolution as a strategic mechanism at banking sectors

Abstract: As the current study has an empirical and impartial nature, a quantitative method was considered the best method for achieving the research objectives of the study. A quantitative technique applied in order to analyze the current study. Sample design refers to the procedure or method the researcher is willing to accept in choosing items for the sample. Research sample was selected using a procedure of random sampling and it was carried out in different banks. A total of 140 questionnaires were distributed, how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…As prior research has suggested, the reasons the cost-based approach is actively used in the pricing mechanism are as follows: (1) cost-related information provides a clear direction toward the possible price range, which guarantees positive profits to firms (Hinterhuber 2004(Hinterhuber , 2016; and (2) in most cases, this type of information is available in the organization, and collecting and understanding the data is easy and clear for any decision maker (Fabiani et al 2005;Govindarajan and Anthony 1983;Guerreiro et al 2006). The findings of this study showed that franchisors consider cost-related information to be useful for setting the prices of business models, thus supporting prior research (e.g., Ali and Anwar 2021;Amaral and Guerreiro 2019). The positive relationship between the cost level and franchise fees suggests that firms with lower cost levels decide lower fees and vice versa.…”
Section: Research Implicationssupporting
confidence: 80%
See 1 more Smart Citation
“…As prior research has suggested, the reasons the cost-based approach is actively used in the pricing mechanism are as follows: (1) cost-related information provides a clear direction toward the possible price range, which guarantees positive profits to firms (Hinterhuber 2004(Hinterhuber , 2016; and (2) in most cases, this type of information is available in the organization, and collecting and understanding the data is easy and clear for any decision maker (Fabiani et al 2005;Govindarajan and Anthony 1983;Guerreiro et al 2006). The findings of this study showed that franchisors consider cost-related information to be useful for setting the prices of business models, thus supporting prior research (e.g., Ali and Anwar 2021;Amaral and Guerreiro 2019). The positive relationship between the cost level and franchise fees suggests that firms with lower cost levels decide lower fees and vice versa.…”
Section: Research Implicationssupporting
confidence: 80%
“…Based on the empirical evidence, Amaral and Guerreiro (2019) mentioned that the cost-based approach is recognized as an essential method for pricing since it also incorporates competitors and value information. Ali and Anwar (2021) specified the cost-based approach into detailed strategies such as penetration pricing, price skimming, and competitive pricing and found them to have substantial magnitudes of influence on the pricing. These findings provide a strong background for understanding that the cost-based approach is identified as the most prevalent method across companies.…”
Section: Prior Research On Pricing Approachesmentioning
confidence: 99%
“…The imbalance between the supply and demand of agricultural products is mainly due to the errors of retailers in estimating market demand. Therefore, it is more realistic to study how a retailer's psychological expectations of online shopping for fresh and live products affect the retailer's decision-making [2]. This experiment will consider the psychological selection behaviour of fresh product buyers of fresh agricultural product retailers.…”
Section: Introductionmentioning
confidence: 99%